It's not necessarily an altitude!

Geometry Level 5

Triangle A B C ABC has two sides A B AB and A C AC such that A B A C = 4 3 \frac{AB}{AC} = \frac{4}{3} . Locate point X X on the third side B C BC such that B X = 2 C X BX = 2CX . Now, let P P be a point on segment A X AX and extend B P BP to meet A C AC at point Y Y . Similarly, extend C P CP to meet A B AB at point Z Z .

If points B , Z , Y , C B, Z, Y, C all lie on a circle, as shown in the diagram, the sum of all possible values of A P P X \frac{AP}{PX} can be written in the form p q \frac{p}{q} , where p p and q q are coprime positive integers.

Find p + q p + q .


The answer is 10.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Shourya Pandey
Jun 14, 2017

We use barycentric coordinates.

As usual, we take A = ( 1 , 0 , 0 ) , B = ( 0 , 1 , 0 ) A=(1,0,0), B=(0,1,0) and C = ( 0 , 0 , 1 ) C=(0,0,1) .

The point X = ( 0 , 1 3 , 2 3 ) X=(0,\frac{1}{3}, \frac{2}{3}) . So the equation of the line A X AX is z = 2 y z=2y . So point P P can be parametrised as

P = ( 1 3 a , a , 2 a ) P= (1-3a,a,2a) . Now the line B P BP has equation 2 a x = ( 1 3 a ) z 2ax = (1-3a)z , so it intersects the line A C AC at the point

Y = ( 1 3 a : 0 : 2 a ) = ( 1 3 a 1 a , 0 , 2 a 1 a ) Y = (1-3a:0:2a)= (\frac{1-3a}{1-a} , 0 , \frac{2a}{1-a}) . Similarly, the point Z = ( 1 3 a 1 2 a , a 1 2 a , 0 ) Z = (\frac{1-3a}{1-2a},\frac{a}{1-2a},0) .

Let the equation of the circle through B , Z , Y B,Z,Y and C C be

a 2 y z b 2 z x c 2 x y + u x + v y + w z = 0 -a^2yz-b^2zx-c^2xy + ux+vy+wz=0 .

Placing the coordinates of B = ( 0 , 1 , 0 ) B=(0,1,0) , we get v = 0 v=0 . Placing the coordinates of C = ( 0 , 0 , 1 ) C=(0,0,1) , we get w = 0 w=0 . Now we place the coordinates of Y Y into the equation. Because y Y = 0 y_Y = 0 , so

b 2 z Y x Y + u x Y = 0 -b^2z_Yx_Y + ux_Y =0 , and because a 1 a \neq 1 (Why?), x Y 0 x_Y \neq 0 . Thus

u = b 2 z Y u = b^2z_Y .

Similarly, by placing the coordinates of Z Z into the equation, we get

u = c 2 y Z u = c^2y_Z . It follows that

b 2 2 a 1 a = c 2 a 1 2 a b^2\frac{2a}{1-a} = c^2\frac{a}{1-2a} . Since c b = 4 3 \frac{c}{b} = \frac{4}{3} , we get

18 a 1 a = 16 a 1 2 a \frac{18a}{1-a} = \frac{16a}{1-2a} , or a = 1 10 a = \frac{1}{10} (again, why is a 0 a \neq 0 ?)

Thus A P P X = x A x P x P x X = 3 a 1 3 a = 3 10 1 3 10 = 3 7 \frac{AP}{PX} = \frac{x_A-x_P}{x_P-x_X} = \frac{3a}{1-3a} = \frac{\frac{3}{10}}{1-\frac{3}{10}} = \boxed{\frac{3}{7}} . Therefore a = 3 , b = 7 , a=3, b=7, and a + b = 10 \boxed{a+b=10} .

Steven Yuan
Jun 11, 2017

For this solution, we will utilize Ceva's Theorem and van Aubel's Theorem .

Firstly, we can apply Ceva's Theorem to get X B X C Y C Y A Z A Z B = 1. \dfrac{XB}{XC} \cdot \dfrac{YC}{YA} \cdot \dfrac{ZA}{ZB} = 1. We also know that Z A Y A = A C A B , \dfrac{ZA}{YA} = \dfrac{AC}{AB}, since B Z Y C BZYC is cyclic. Combining these with the given statements, we have

X B X C Y C Y A Z A Z B = 1 2 Y C Y A Z A Z B = 1 Y C Y A Z A Z B = 1 2 Y C Z B Z A Y A = 1 2 Y C Z B A C A B = 1 2 Y C Z B 3 4 = 1 2 Y C Z B = 2 3 . \begin{aligned} \dfrac{XB}{XC} \cdot \dfrac{YC}{YA} \cdot \dfrac{ZA}{ZB} &= 1 \\ 2 \cdot \dfrac{YC}{YA} \cdot \dfrac{ZA}{ZB} &= 1 \\ \dfrac{YC}{YA} \cdot \dfrac{ZA}{ZB} &= \dfrac{1}{2} \\ \dfrac{YC}{ZB} \cdot \dfrac{ZA}{YA} &= \dfrac{1}{2} \\ \dfrac{YC}{ZB} \cdot \dfrac{AC}{AB} &= \dfrac{1}{2} \\ \dfrac{YC}{ZB} \cdot \dfrac{3}{4} &= \dfrac{1}{2} \\ \dfrac{YC}{ZB} &= \dfrac{2}{3}. \end{aligned}

Now, we focus on B Z P \triangle BZP and C P Y . \triangle CPY. Because B Z P = P Y C \angle BZP = \angle PYC and Z B P = P C Y \angle ZBP = \angle PCY due to the cyclic nature of B Z Y C , BZYC, we get B Z P C P Y . \triangle BZP \sim \triangle CPY. This means

Y C Z B = C P B P = P Y P Z = 2 3 , \dfrac{YC}{ZB} = \dfrac{CP}{BP} = \dfrac{PY}{PZ} = \dfrac{2}{3},

which we had found previously.

By van Aubel's Theorem,

C P P Z = C X X B + C Y Y A = 1 2 + C Y Y A B P P Y = B X X C + B Z Z A = 2 + B Z Z A . \dfrac{CP}{PZ} = \dfrac{CX}{XB} + \dfrac{CY}{YA} = \dfrac{1}{2} + \dfrac{CY}{YA} \\ \dfrac{BP}{PY} = \dfrac{BX}{XC} + \dfrac{BZ}{ZA} = 2 + \dfrac{BZ}{ZA}. \\

Dividing the top equation by the bottom yields

1 2 + C Y Y A 2 + B Z Z A = C P P Z P Y B P = C P B P P Y P Z = 2 3 2 3 = 4 9 . \begin{aligned} \dfrac{\frac{1}{2} + \frac{CY}{YA}}{2 + \frac{BZ}{ZA}} &= \dfrac{CP}{PZ} \cdot \dfrac{PY}{BP} \\ &= \dfrac{CP}{BP} \cdot \dfrac{PY}{PZ} \\ &= \dfrac{2}{3} \cdot \dfrac{2}{3} \\ &= \dfrac{4}{9}. \end{aligned}

Let a = C Y Y A , b = B Z Z A . a = \dfrac{CY}{YA}, b = \dfrac{BZ}{ZA}. The relationship above simplifies into, 1 2 + a = 4 9 ( 2 + b ) . \dfrac{1}{2} + a = \dfrac{4}{9} (2 + b). However, by Ceva's, we also know that Y C Y A Z A Z B = 1 2 , \dfrac{YC}{YA} \cdot \dfrac{ZA}{ZB} = \dfrac{1}{2}, so a = 1 2 b . a = \dfrac{1}{2}b. Solving this system of equations yields ( a , b ) = ( 7 2 , 7 ) . (a, b) = \left ( \dfrac{7}{2}, 7 \right ).

Finally, applying van Aubel's Theorem again, we have

A P P X = A Z Z B + A Y Y C = 1 b + 1 a = 1 7 + 2 7 = 3 7 . \begin{aligned} \dfrac{AP}{PX} &= \dfrac{AZ}{ZB} + \dfrac{AY}{YC} \\ &= \dfrac{1}{b} + \dfrac{1}{a} \\ &= \dfrac{1}{7} + \dfrac{2}{7} \\ &= \dfrac{3}{7}. \end{aligned}

Since we never made any assumptions about A B C \triangle ABC other than what was stated in the problem, we see that A P P X = 3 7 \dfrac{AP}{PX} = \dfrac{3}{7} is the only solution that achieves our desired results, so p + q = 10 . p + q = \boxed{10}.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...